A comparative effectiveness study of adalimumab, etanercept and infliximab in biologically naive and switched rheumatoid arthritis patients: results from the US CORRONA registry. Issue 7 (30th January 2012) - Greenberg, Jeffrey D; Reed, George; Decktor, Dennis; Harrold, Leslie; Furst, Daniel; Gibofsky, Allan; DeHoratius, Ralph; Kishimoto, Mitsumasa; Kremer, Joel M
Abstract : Purpose: To compare the effectiveness of anti-tumour necrosis factor (TNF) agents in biologically naive and 'switched' rheumatoid arthritis (RA) patients. Methods: RA patients enrolled in the CORRONA registry newly prescribed adalimumab (n=874), etanercept (n=640), or infliximab (n=728) were stratified based on previous anti-TNF use. Clinical effectiveness at 6, 12 and 24 months was examined using the modified American College of Rheumatology response criteria (mACR20/50/70) and achievement of remission (28-joint disease activity score (DAS28) and clinical disease activity index (CDAI)) in unadjusted and adjusted analyses. The persistence of anti-TNF treatment was examined using Cox proportional hazard models. Results: Among 2242 patients (1475 biologically naive, 767 switchers), mACR20, 50 and 70 responses were similar (p>0.05) for adalimumab, etanercept and infliximab at all time points, as were rates of CDAI and DAS28 remission (p>0.05). Response and remission outcomes were consistently inferior for switched versus biologically naive patients. The adjusted OR for achieving an mACR20 response was 0.54 (95% CI 0.38 to 0.76) in first-time switchers and 0.42 (95% CI 0.23 to 0.78) in second-time switchers versus biologically naive patients at 6 months. The adjusted OR for achieving DAS28 remission were 0.29 (95% CI 0.15 to 0.58) for first-time switchers and 0.26 (95% CI 0.08 to 0.84) for second-time switchers. Persistence was higher in biologically naive patients, for whom persistence was highest with infliximab. Conclusions: No differences in rates of drug response or remission were observed among the three anti-TNF. Infliximab was associated with greater persistence in biologically naive patients. Response, remission and persistence outcomes were diminished for patients who switched anti-TNF.